3Z-2Z+16=4

Simple and best practice solution for 3Z-2Z+16=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3Z-2Z+16=4 equation:


Simplifying
3Z + -2Z + 16 = 4

Reorder the terms:
16 + 3Z + -2Z = 4

Combine like terms: 3Z + -2Z = 1Z
16 + 1Z = 4

Solving
16 + 1Z = 4

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 1Z = 4 + -16

Combine like terms: 16 + -16 = 0
0 + 1Z = 4 + -16
1Z = 4 + -16

Combine like terms: 4 + -16 = -12
1Z = -12

Divide each side by '1'.
Z = -12

Simplifying
Z = -12

See similar equations:

| a^2-16ab+63b^2=0 | | 8-5x=-7x+10 | | v-14=u | | 9x^4-6x^3+7/-9x^4=0 | | 2y+3=14 | | 15b^2+6b-3= | | 5x^2=3x+2 | | 7x-5=22-2x | | x^2+5x+6=09 | | -7tx=b-3y | | 108z+3-64z+5= | | 25x^2=30x-9 | | 0=3x^2-17x+20 | | -3x^6+6x^6= | | Z-2(1-Z)-2Z= | | 6x^8+4x^8= | | 3(Y-2)-2(Y-6)= | | -15=x^2+8x | | -1/7+Y=5/7 | | 10x^8+3x^6= | | 6=7b-pb | | 50c+349-200=400 | | 28x^2-18x+72=0 | | -2v-22=-8(v-1) | | -2(u+6)=-8u+48 | | -(x+8)(x-9)=-52 | | 9x+12=-6(x+3) | | 22=5(w+6)+3w | | 6(x-4)-2x=-4 | | -10=5(y+8)+5y | | 18+4(3G-7)=-70 | | 64in^2=12.6(h) |

Equations solver categories